2008
DOI: 10.1089/acm.2007.0786
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture in the Treatment of Chronic Obstructive Pulmonary Disease

Abstract: This study demonstrated that acupuncture contributed to the reduction of COPD-related dyspnea on exercise in 15 matched-pair parallel subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 25 publications
1
47
0
2
Order By: Relevance
“…Our review clarified that weaker study designs may bias study results and overestimate positive effects of the treatment -consistent with the findings of Martin et al 47 Despite the weaknesses observed, some studies demonstrated the potential of acupuncture in the sense that it may be effective in treating certain diseases, such as COPD 41 and UIP, 33 which are currently incurable by modern medicine. Likewise, some papers suggested a possibility of using acupuncture in health promotion, such as cold prevention.…”
Section: Original Papersupporting
confidence: 86%
See 2 more Smart Citations
“…Our review clarified that weaker study designs may bias study results and overestimate positive effects of the treatment -consistent with the findings of Martin et al 47 Despite the weaknesses observed, some studies demonstrated the potential of acupuncture in the sense that it may be effective in treating certain diseases, such as COPD 41 and UIP, 33 which are currently incurable by modern medicine. Likewise, some papers suggested a possibility of using acupuncture in health promotion, such as cold prevention.…”
Section: Original Papersupporting
confidence: 86%
“…39-41 43 44 For COPD, one study 41 with Jadad score of zero, found acupuncture superior to drugs, but was not supported by an N-of-1 study. 40 For asthma, one n-of-1 study 39 suggested acupuncture may have an effect compared with drugs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are minimal data about the effectiveness of alternative and complementary medicine in relieving breathlessness (247). In two small studies in patients with COPD, acupuncture was associated with a significant reduction in breathlessness (282,283). However, a third study reported no benefit (284), and no benefit was found in a recent study of patients with advanced cancer (285).…”
Section: Treatmentmentioning
confidence: 99%
“…5 We have previously demonstrated that respiratory function evaluated with Borg scale scores and the 6 min walking distance (6MWD) could be markedly improved with acupuncture in a prospective matched-pair trial that included patients treated with acupuncture and those receiving standard medication. 6 However, differences in the effect of acupuncture between subgroups classifi ed according to disease severity are unclear. In addition, the manner in which acupuncture affects disease prognosis has not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%